Animal Research in Higher Education: Engaging the Moral and Ethical Conversation. Issue 1 (2nd January 2017) - Dolby, Nadine
Abstract: Faculty and staff are rightly concerned with the moral and ethical dimensions of human relationships on campus. Yet, they rarely discuss the animals with whom they share their campuses and larger world. In this article, the author reflects on her experience on an Institutional Animal Care and Use Committee to raise questions about animals in higher education research, amid changing understandings of human/animal relationships, and growing scientific evidence of animal cognition and emotion. In conclusion, the author suggests that faculty and staff and students need to engage these conversations to be informed, involved citizens and whole human beings.